Pemberdayaan Pengetahuan Masyarakat Mengenai Mikroba dan Lingkungan di Masa Pandemi - Aidha Zulaika; Sari Sekar Ningrum; Nur Fitriyani Sahamony; Tri Panji (Universitas Pahlawan Tuanku Tambusai, 2023)
The outbreak of the Covid-19 Pandemic that spread throughout the world caused by sars virus infection has resulted in people being wary of viral or microbial spreading. In addition, there is relationship of environmental conditions and the survival and the transmission of microbes. Especially in various environmental problems caused by microbial pollution. Empowering community knowledge of the relationship between microbes and the environment is needed to build an insightful and wise society to respond to The existence and the spreading of microbial in the environment. The method used in this activity is knowledge sharing by organizing webinar consisting of three stages, namely pretest, online education using google meet and postest using google form. Data processing by excel calculations, the results of increasing knowledge after the knowledge sharing were obtained, namely 90.81% comparing with before knowledge sharing namely 87.75%, although overall there is an increase in public knowledge. Thus, knowledge sharing or knowledge counseling can be said to be effective for increasing public knowledge.